Crop wild relatives conservation in the Chechen Republic - L. V. Bagmet; M. A. Taisumov (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. Plant genetic resources (PGR) conservation is an indispensable condition for ensuring the country's economic and environmental security. The most important component of the PGR status assessment is the study of crop wild relatives in a particular region. This is especially important for the Chechen Republic due to its unique geographic, climatic, environmental and political conditions.Materials and methods. The material for the present research was taken from the published data on the flora of the studied region and the own field studies conducted by the route exploration method. In order to select priority species for conservation, the items of the methodology for PGR conservation adapted for Russia were used. The map of species locations was built using MapInfo 8.5.Results and conclusions. Within the framework of the work on inventoring crop wild relatives (CWR) in the regions of Russia, they were studied in the natural plant communities of the Chechen Republic. A list of 468 species belonging to 120 genera of 35 families has been compiled, which covers over 20% of the entire flora of the republic. Based on the analysis of the CWR species distribution in the studied area, assessment of their economically and biologically important traits, as well as according to the criteria of rarity and vulnerability, a preliminary list has been drawn up for the inclusion in the CWR Red List of the Russian Caucasus. For some species, a map of their location in the studied area was created. For effective CWR preservation, it is recommended to use two methods, that is, in situ and ex situ conservation. However, to date, a more realistic way to preserve valuable species from local populations is to include them in the VIR collection. The Specially Protected Natural Territories (SPNT) System that currently exists in the republic does not provide the necessary protection for natural complexes and individual plant species. The results of the performed study can serve as an additional reason for the establishment of a Chechen State Natural Complex Reserve in the republic.